- Implementasi Reaksi Metanogenesis sebagai Materi Pembelajaran Kimia pada Pelajaran Kimia SMA dengan Pendekatan Chemistry, Life, Universe, and Everything (CLUE) - Oktavianti, Nur Azlina; Martoprawiro, Muhamad Abdulkadir; Rattyananda, Badra Sanditya (Jurnal Penelitian Pendidikan IPA, 2024)
Palm Oil Mill Effluent (POME) is the biggest waste from palm oil production. This liquid waste contain much methane gas (CH4) which has potential as renewable energy, namely biogas. The last stage of processing biogas called methanogenesis reaction, the process of synthesis methane and carbon dioxide. The methanogenesis reaction can be studied by computational studies as learning media source for SeniorHigh School Chemistry with the Chemistry, Life, Universe, and Everything (CLUE) approach. According to learning outcomes of Merdeka Curriculum, the methanogenesis reaction can be used as a learning source forthree chapters in F phase. The chapters areChemical Bonding, Rate of Reaction,and Thermochemistry. The chapter of Chemical Bonding describe hydrogen bonding in acetic acid intermediate species and its effect on the molecular characteristics. The chapter Rate of Reactiondiscuss the result of computational calculation to determine the activation energy (AE). Methanogenesis reaction have two transition states (TS), with AE of each TS are 228.56 kJ.mol-1 and 281.31 kJ.mol-1, while the second stage act as the rate-determining step. The last, for Thermochemistry chapter, the content material is define the quantity of thermodynamic variables on methanogenesis reaction.The value of∆S = 50.14 kJ.mol-1T, ∆G = 139.7 kJ.mol-1, and ∆H =168.84 kJ.mol-1.